Penyuluhan Literasi Keuangan di Era Digital Untuk Mensukseskan Keputusan Investasi Santri Pondok Pesantren Monash Institute di Ngaliyan Semarang - Bahri, Saiful; Maskudi; Karsiati; Arwani, Mokhamad; Sunarto (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
This community service program was carried out with the aim of improving the financial literacy of students at the Monash Institute Islamic Boarding School. Through financial literacy counseling in the digital era, this program aims to equip santri with the knowledge and skills needed to make wise investment decisions. The counseling integrates modern educational approaches with Islamic financial practices, adapting to the values espoused by the pesantren. It is expected that through this program, santri can improve their understanding of personal and institutional financial management in a sharia context.